2016
DOI: 10.1111/iej.12712
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium hypochlorite and saline on cyclic fatigue resistance of WaveOne Gold and Reciproc reciprocating instruments

Abstract: Immersion of WaveOne Gold and Reciproc reciprocating instruments in saline and NaOCl solutions decreased considerably their cyclic fatigue resistance. The fatigue resistance of WaveOne Gold instruments was higher than that of Reciproc instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 36 publications
2
35
0
2
Order By: Relevance
“…Furthermore, to a certain extent the use of different lubricants during testing may be responsible for the inconsistent results (Elnaghy & Elsaka , Uslu et al ). When assessing Reciproc instruments in air fracture occurred after 1251 cycles, in sodium hypochlorite it occurred after only 882 cycles (Elnaghy & Elsaka ). This difference is nearly 250%.…”
Section: Results For the Same Instrument In Different Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, to a certain extent the use of different lubricants during testing may be responsible for the inconsistent results (Elnaghy & Elsaka , Uslu et al ). When assessing Reciproc instruments in air fracture occurred after 1251 cycles, in sodium hypochlorite it occurred after only 882 cycles (Elnaghy & Elsaka ). This difference is nearly 250%.…”
Section: Results For the Same Instrument In Different Studiesmentioning
confidence: 99%
“…A 100% increase in speed has been demonstrated to result in a 30% reduction in terms of NCF (Lopes et al 2009). Furthermore, to a certain extent the use of different lubricants during testing may be responsible for the inconsistent results (Elnaghy & Elsaka 2017b. When assessing Reciproc instruments in air fracture occurred after 1251 cycles, in sodium hypochlorite it occurred after only 882 cycles (Elnaghy & Elsaka 2017b).…”
Section: Results For the Same Instrument In Different Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…DSC analysis of ProTaper Gold revealed approximately 50°C for austenite finish temperature (Hieawy et al 2015), indicating that these instruments also mainly contain martensite or Rphase under clinical conditions. All Gold and Blue heat-treated files demonstrated enhanced flexibility and fatigue resistance compared with conventional NiTi and M-Wire instruments , Nguyen et al 2014, Plotino et al 2014b, 2017Duke et al 2015, Hieawy et al 2015, Elnaghy & Elsaka 2016a, 2017a, Kaval et al 2016 Kaval et al (2016) reported that ProTaper Gold had a significantly higher maximum torque than Hyflex EDM and ProTaper Universal (Dentsply Sirona Endodontics), whilst Hyflex EDM had an increased distortion angle. ProTaper Gold was found to be more effective in lateral cutting action than ProTaper Universal (Vasconcelos et al 2018).…”
Section: Gold and Blue Heat-treated Instrumentsmentioning
confidence: 99%
“…During instrumentation, interruption of file movement within a root canal could occur in several clinical scenarios (Elnaghy & Elsaka 2016). Electronic apex locator integrated endodontic motors stop the instrument when the working length is reached to prevent over instrumentation (Siu et al 2009).…”
Section: Introductionmentioning
confidence: 99%